First molecular detection of porcine circovirus type 4 (PCV4) in Malaysia - Tan, C.Y.; Thanawongnuwech, R.; Arshad, S.S.; Hassan, L.; Lee, C.Y.; Low, S.E.; Fong, W.C.M.; Ooi, P.T. (Malaysian Society of Parasitology and Tropical Medicine, 2023)
Porcine circovirus type 4 (PCV4) is the newest member in the porcine circovirus family, first reported in 2020. To date, the presence of PCV4 has only been reported in China, South Korea and most recently in Thailand. Detection of PCV4 have been reported in various production stages of pigs from piglets, finishers to sows; associated with a myriad of clinical manifestations including porcine dermatitis and nephropathy syndrome (PDNS), postweaning multisystemic wasting syndrome (PMWS), respiratory, enteric and neurological diseases. While successful virus isolation and culture has yet to be reported, pathogenicity of PCV4 has been demonstrated through infectious clone studies. The objective of this study is to investigate the presence of PCV4 in Malaysian porcine population to update the epidemiology of porcine circoviruses in Malaysia. A total of 49 samples from commercial intensive pig farms, abattoir and wild boar population were subjected to conventional polymerase chain reaction assay to detect PCV4 capsid (cap) genome. Resulting cap nucleotide sequences were analyzed for maximum likelihood phylogeny relationship. Results revealed that PCV4 is present in Peninsular Malaysia at a molecular prevalence of 4.08% (2 / 49 samples). Both PCV4 positive samples originated from clinically healthy finishers. Malaysian PCV4 strains were classified as genotype PCV4b, and were found to be phylogenetically distinct from the China, South Korea and Thailand strains. With this latest update of the novel PCV4 in Malaysia, it is clear that more attention needs to be given to the investigation of novel porcine circoviruses (PCV) and management of PCV diseases.